2019
DOI: 10.18632/oncotarget.27390
|View full text |Cite
|
Sign up to set email alerts
|

ISG15 induction is required during L1-mediated colon cancer progression and metastasis

Abstract: Hyperactivation of Wnt/β-catenin target gene expression is a hallmark of colorectal cancer (CRC) development. We identified L1-CAM (L1) and Nr-CAM, members of the immunoglobulin family of nerve cell adhesion receptors, as target genes of the Wnt/β-catenin pathway in CRC cells. L1 overexpression in CRC cells enhances their motile and tumorigenic capacity and promotes liver metastasis. L1 is often localized at the invasive edge of CRC tissue. Using gene arrays and proteomic analyses we identified downstream sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
(42 reference statements)
0
12
1
Order By: Relevance
“…In previous studies, we have shown that the increase in the expression of various genes in CRC cells following L1 transfection operates by a mechanism that involves cooperation between ezrin and NF-κB signaling [ 7 , 10 , 12 , 13 ]. Since the induction of PLOD2 by L1 depends on ezrin ( Supplementary Table S1 ), we wished to determine the downstream effectors of the ezrin-mediated increase in PLOD2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we have shown that the increase in the expression of various genes in CRC cells following L1 transfection operates by a mechanism that involves cooperation between ezrin and NF-κB signaling [ 7 , 10 , 12 , 13 ]. Since the induction of PLOD2 by L1 depends on ezrin ( Supplementary Table S1 ), we wished to determine the downstream effectors of the ezrin-mediated increase in PLOD2.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of genes induced by L1 expression in CRC cells revealed a number of genes known as intestinal stem cell signature genes [ 5 , 6 , 7 , 8 , 9 ]. We identified also additional L1-induced genes [ 10 , 11 , 12 ] that were all shown to be necessary for promoting the tumorigenesis and metastasis of CRC cells by L1 expression. A common signaling pathway activating these genes by L1 overexpression involves the cytoskeletal actin-binding protein ezrin and the NF-κB pathway [ 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another protein whose level is elevated in the secretome of CRC cells is the ubiquitin-like interferon induced gene 15 (ISG15), which operates much like ubiquitin by conjugating to target proteins (ISGylation) [ 63 ]. We found that increased ISG15 levels were required for L1-mediated CRC progression because suppression of ISG15 expression blocked the L1-mediated increase in CRC cell motility, tumorigenesis, and metastasis [ 63 ]. The induction of ISG15 was dependent on proper L1–L1 mediated adhesions, as point mutations in the L1 ectodomain abolished its ability to induce the expression of ISG15 [ 63 ].…”
Section: Secreted Factors That Promote the Tumorigenesis Induced Bmentioning
confidence: 99%
“…We found that increased ISG15 levels were required for L1-mediated CRC progression because suppression of ISG15 expression blocked the L1-mediated increase in CRC cell motility, tumorigenesis, and metastasis [ 63 ]. The induction of ISG15 was dependent on proper L1–L1 mediated adhesions, as point mutations in the L1 ectodomain abolished its ability to induce the expression of ISG15 [ 63 ]. The induction in ISG15 by L1 was dependent on the NF-κB pathway and ISG15 was detected in CRC tumor tissue and in the adjacent stroma, but not in normal colonic mucosa, suggesting that ISG15 could serve as a therapeutic target for CRC treatment [ 63 ].…”
Section: Secreted Factors That Promote the Tumorigenesis Induced Bmentioning
confidence: 99%
See 1 more Smart Citation